Engineering the Oleaginous Yeast Rhodosporidium toruloides for Improved Resistance Against Inhibitors in Biomass Hydrolysates - Lyu, Liting; Chu, Yadong; Zhang, Sufang; Zhang, Yue; Huang, Qitian; Wang, Shuang; Zhao, Zongbao K. (Frontiers in Bioengineering and Biotechnology, 2021)
Conversion of lignocellulosic biomass into lipids and related chemicals has attracted much attention in the past two decades, and the oleaginous yeast Rhodosporidium toruloides has been widely used in this area. While R. toruloides species naturally have physiological advantages in terms of substrate utilization, lipid accumulation and inhibitor resistance, reduced lipid production and cell growth are noticed when biomass hydrolysates are used as feedstocks. To improve the robustness of R. toruloides, here we devised engineered strains by overexpressing genes responsible for phenolic compounds degradation. Specifically, gene expression cassettes of manganese peroxidase gene (MNP) and versatile peroxidase gene (VP) were constructed and integrated into the genome of R. toruloides NP11. A series of engineered strains were evaluated for lipid production in the presence of typical phenolic inhibitors. Results showed that R. toruloides strains with proper expression of MNP or VP indeed grew faster in the presence of vanillin and 5-hydroxymethylfurfural than the parental strain. When cultivated in concentrated mode biomass hydrolysates, the strain VP18 had improved performance as cell mass and lipid content increased by 30% and 25%, respectively. This study provides more robust oleaginous yeast strains for microbial lipid production from lignocellulosic biomass and similar efforts may be used to devise more advanced lipid producers.